Microbial purity of recycled fibers made from printed offset paper and nanomodified polycaprolactone coated paperboard - Vukoje, Marina; Bolanča Mirković, Ivana; Željković, Petra (Journal of Print and Media Technology Research, 2022)
In order to increase the sustainability of paper or board production, it is desirable to use recycled fibers as much as possible. Microorganisms are in a smaller or higher amount present on the surface of paper or paperboard, so they are also present in the paper pulp or on the cellulose fibers. The purity of the mentioned fibers is important for obtaining a quality raw material that is health conforming. The aim of this study is to determine the microbiological quality of recycled fibers obtained by recycling of paper and paperboard intended for the manufacture of packaging products. Samples were in an average microbiological environment without food exposure. Quality of recycled fibers was studied through the total number of bacteria and determined for different recycled samples. The total number of microorganisms was estimated by both the disintegration and smear method. Results showed that only the disin- tegration method was suitable for the evaluation since the smear method did not produce any results. Moreover, the disintegration method was suitable only for the determination of bacteria alone, since no growth of molds or yeast occurred. In addition, the influence of paper composition, paperboard coatings and recycling methods on bacterial growth is demonstrated. The number of bacteria obtained on recycled fibers is affected by the presence of nanopar- ticles in coatings (Zn, Si and Al), as well as by the presence of different components in the base paper.